The Semiotic Meaning Of The Giant Statue of Mazu And The Place On Meizhou Island Of China - Ke Yihan, Peera Phanlukthao, Mateta Sirisuk (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article briefly describes the geographical environment of Meizhou Island, analyzes the origin and aesthetic characteristics of the giant statue of Mazu, and focuses on its semiotic meaning from the perspective of the giant statue of Mazu as a visual image resource, it has function of education, this is conducive to develop Mazu culture.